2022
DOI: 10.1002/aenm.202201109
|View full text |Cite
|
Sign up to set email alerts
|

Field Effect Passivation in Perovskite Solar Cells by a LiF Interlayer

Abstract: as higher PCEs have been achieved due to lower parasitic absorption losses, [4,5] and their low-temperature processing enables a wider choice of bottom cells.The device stability and PCE of silicon/perovskite tandem solar cells are crucially determined by the quality of the contact layer interfaces, [6,7] as they are found to limit especially the open circuit voltage (V OC ) and fill factor. Charge carrier selective contacts and their interfaces toward MHP absorbers are thus a field of recent and ongoing resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
79
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 58 publications
8
79
0
Order By: Relevance
“…However, interfacing the perovskite layer with C60 substantially lowers ∆EF possibly by introducing additional interfacial defects as suggested by refs. 23,24 and consistent with previous reports on steady state 25 and transient photoluminescence 15,26 . OAI modification can effectively passivate the perovskite/C60 interface defects, as samples with the perovskite/C60 interface show a stronger enhancement in ∆EF after OAI modification than stacks without C60.…”
Section: Influence Of Charge Extracting Layerssupporting
confidence: 92%
“…However, interfacing the perovskite layer with C60 substantially lowers ∆EF possibly by introducing additional interfacial defects as suggested by refs. 23,24 and consistent with previous reports on steady state 25 and transient photoluminescence 15,26 . OAI modification can effectively passivate the perovskite/C60 interface defects, as samples with the perovskite/C60 interface show a stronger enhancement in ∆EF after OAI modification than stacks without C60.…”
Section: Influence Of Charge Extracting Layerssupporting
confidence: 92%
“…However, the non-radiative recombination at the perovskite/C 60 interface and the involved defect states remain fundamentally poorly understood 9 12 . Recent results in this regard have shown that recombination occurs predominantly across the interface 12 , likely due to a small energy level offset between the conduction band minimum of the perovskite and the lowest unoccupied molecular orbital (LUMO) level of C 60 13 , or charge transfer states at the interface 12 , 14 . Thus, it is critical to improve the energy alignment, passivate defects on the perovskite surface or repel minority carriers from the interface.…”
Section: Introductionmentioning
confidence: 99%
“…By utilizing CFSYS, the field-effect passivation ability of the LiF interlayer at the perovskite/C 60 interface was demonstrated, which resulted in a mild dipole effect and fixed charges that lowered the hole concentration in the vicinity of the interface. 131…”
Section: Characterization Techniques Of Passivation Strategiesmentioning
confidence: 99%
“…67,126 The constant final state yield spectroscopy (CFSYS) was recently applied to investigate the electronic interface formation and energy level alignment between perovskite and ETL in inverted PCSs, in order to confirm field-effect passivation. 131 This characterization is achieved by applying UPS with specific excitation energy and additionally varying the incident photon energy in the near-UV range and measuring the excited photoelectrons per absorbed photon (yield) at one constant final state (fixed kinetic energy). Through directly observing the Fermi edge in the CSFYS spectra, the measurement-induced surface photovoltage effects in the photoactive layer stacks and the energetic positions to the actual surface Fermi level can be accounted.…”
Section: Characterization For Field-effect Passivationmentioning
confidence: 99%